APLIKASI MATCHMAKER ADOPSI HEWAN PELIHARAAN (OPet) BERBASIS ANDROID MENGGUNAKAN METODE MACHINE LEARNING - Wijaya Kusuma Yasa, Kadek; Nunut Asihanna, Ester; Sudarma, Made; Care Khrisne, Duman; Arsa Suyadnya, I Made (Program Studi Teknik Elektro UNUD, 2024)
The importance of pet adoption is very important in efforts to support the prevention of animal abandonment. Currently, the pet adoption system in Indonesia still largely relies on a manual approach. This process is carried out directly without paying attention to important aspects of the match between the pet and its adopter, which can result in a lack of information which has a long-term impact on the abandonment or return of the pet. Based on these problems, this research aims to design and create an application that can facilitate the pet adoption process. This application was built for Android-based mobile devices by utilizing Machine Learning methods to provide personalized pet recommendations based on user preferences using Content-Based Filtering and making it easier to identify pet breeds from photos uploaded or selected by users using Image Classification. The pet data collected was sourced from the Kaggle, TensorFlow, and GitHub websites. It is hoped that the results of this research can overcome the problem of pet adoption in a better and more sustainable way and will not only provide benefits for abandoned animals, but can also reduce cases of animal abandonment due to irresponsible owners.